Implementing Digital Public Services: Bridging the Gap Between Transformational Ambitions and Local Bureaucratic Capacity - Siti Marwiyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The government carries out its functions within the bureaucracy as a public institution, particularly in public services. The digitalization of public services refers to the application of information and communication technology in the process of providing services to the public. The concept of e-government in Indonesia is embodied in the SPBE policy. The SPBE policy has been implemented in both the central and regional governments. However, empirically, the implementation of SPBE at the regional government level shows a significant disparity. There is a gap between the ambitions in implementation and the capacity of the bureaucracy. This is interesting to study, especially to understand the implementation of digital public services related to the gap between transformation ambitions and the capacity of the regional bureaucracy. This study uses a qualitative-descriptive literature review method. This method was chosen to systematically and critically examine various written sources relevant to the SPBE topic in the context of the gap between transformation ambitions and the capacity of the regional bureaucracy. The results show that the implementation of SPBE shows a significant gap between the ambitions of digital transformation formulated nationally and the actual capacity of the bureaucracy at the regional level.